Implementation Of IoT In Nila Fish Cultivation With Bioflock System - Wasito, Endro; Prahara, Tahan; Nursyahid, Arif; ., Dadi; Anggraeni K., Sri (JAICT, 2024)
In cultivating tilapia using the biofloc system, maintaining water quality (temperature, pH, turbidity) is not only for the health of the fish but also for the reproduction of the biofloc. So that water quality is known, sensors connected to IoT are installed. Sensor output data is processed by Arduino and sent to a data base server via the internet network so that water quality parameters can be monitored at any time via the internet network. This system was created in research entitled "Optimizing Tilapia Cultivation of Biofloc Systems with the Internet of Things". The pool has a diameter of 2m, height 1m, airator 500 liters/min, 4 airstones @ 30 liters/min. After the pond is assembled and the biofloc has grown (made from 375 ml multi-probiotic, 300 ml molasses, 150 gram dolomite, 60 gram nitrobacter), proceed with adding 150 tilapia fish seeds 5-6 cm long (weight 22.2 gr/fish). After 2 months the growth of the tilapia became 12-13 cm long (weighing 100 g/fish), with 2% mortality. The sensor measurement results displayed on the website are as follows: average pH values (5.6-7.5), temperature (27-29), turbidity (225-354) ppm, floc density (20-25) ml/liter. Hiprofit 781-3 feed is 13.4 kg. The research results show that IoT implementation can display the water quality of biofloc tilapia ponds in real time. pH fluctuations from 5.6-7.5 indicate that biofloc can function well.